PEMBERDAYAAN KARUNIA MOTIVASI BERDASARKAN ROMA 12:1-8 DALAM PELAYANAN JEMAAT - Fanny Fanny; Rudyanto Chandra Saputra; Gregorius Suwito (JOURNAL of THEOLOGICAL STUDENTS, 2022)
The gifts of the Spirit are a special ability bestowed by God and channeled by the Holy Spirit to believers for Christian devotion. The gifts of the Holy Spirit are not rewards, but gifts of voluntary work done by the Holy Spirit as equipment for service both internally and externally gifts of the Spirit are given according to the Holy Spirit's sovereign will. According to his will and his sovereignty for believers to build up the body of Christ, one with another. After the researchers conducted research in the field, the results obtained stated that the level of empowerment of the gift of motivation based on Romans 12:1-8 in the ministry of the congregation at GBT Rambakulu is based on the calculation of the sample obtained a value of 90,01%